LEGAL PROTECTION OF CONSUMERS USING E-MONEY IN VIEW FROM LAW NUMBER 8 OF 1999 REGARDING CONSUMER PROTECTION - Leomongga Alamsyah Sitompul; Saidin Saidin; T. Keizerina Devi A; Jelly Leviza (NOMOI Law Review, 2023)
One of the problems that arise for consumers or electronic money holders is card damage. Card damage usually occurs in chip-based electronic money types. Damage to the card causes failure in payment transactions because electronic money cannot be read by the reader at the merchant where the transaction is made, resulting in a failed transaction. The type of research used in this discussion is normative juridical research, namely to provide an understanding that law is a statutory instrument that is regulatory in its implementation. Furthermore, the data obtained is presented descriptively and then analyzed qualitatively. The results of the study show that a form of legal protection for users of Electronic Money (e-money) for the loss of e-money cards so that they are used by unauthorized parties is the Consumer Protection Act which gives e-money users the right to file a claim for compensation to the district court. or Consumers can also bring this problem to the Consumer Dispute Settlement Agency (BPSK). The legal position of e-money users in filing lawsuits related to the Consumer Protection Act is that electronic money users are consumers in the banking sector, so they have rights and obligations in using e-money products.